Coagulation profile in hospitalized children with COVID-19: pediatric age dependency and its impact on long COVID development - Boyarchuk, Oksana; Perestiuk, Vita; Kosovska, Tetyana; Volianska, Liubov (Frontiers in Immunology, 2024)
Pulmonary endotheliopathy and microvascular immunothrombosis play a key role in acute COVID-19. Moreover, persistent endotheliopathy and heightened coagulability frequently occur in individuals recovering from COVID-19, suggesting the intriguing possibility of their role in the development of long COVID. The aim of our study was to investigate the coagulation profile in patients with COVID-19 based on age and their role in the development of long COVID.We conducted a prospective single-center cohort study from September 2022 to August 2023. The study involved 190 patients younger than 18 years who were hospitalized at the Ternopil City Children's Hospital, Ukraine due to COVID-19. Patients underwent determination of coagulation profile in addition to the general clinical examination. After discharge from the hospital, patients were monitored for the presence of long COVID symptoms. Among the 157 participants who consented for follow-up, 62 patients (39.5%) had long COVID symptoms according to the WHO definition, while the rest (95 patients) did not have symptoms of long COVID (fully recovered).The study revealed the normal count of platelets in the majority of patients (86.8%), whereas abnormalities in the coagulation profile were revealed in 94.5% of children with COVID-19, and these changes were age-dependent. The patients were mostly presented with increased activated partial thromboplastin time (69.1%), prothrombin time (PT) (39.8%) and D-dimer (45.0%). There was no significant difference between the median of platelet levels and coagulation profile indicators between the groups with long COVID and recovered. Among children who developed persistent long COVID symptoms there was a statistically higher percentage of abnormal PT values (53% versus 36.1%, p=0.0432), with no significant differences in other coagulation profile indicators. Abnormal PT along with female gender, comorbidities, especially allergic pathology, nutritional disorder, including obesity, were determined as potential risk factors of the long COVID development (Odds ratio -2.0611; 95% 1.0179-4.1737, p=0.0445).The study highlights the need for more extensive research into the coagulation profiles of pediatric populations, considering age-specific factors. This could enhance our understanding of thromboinflammation in COVID-19 and its potential contribution to the development of persistent symptoms.